Long-term field-realistic exposure to a next-generation pesticide, flupyradifurone, impairs honey bee behaviour and survival - Simone Tosi (Nature Portfolio, 2021)
Tosi and colleagues perform a large, multinational experiment on honey bees, encompassing multiple subspecies, to assess the short- and long-term effects of a next-generation pesticide, flupyradifurone, on this key pollinator species. Their findings indicate that this “bee safe” pesticide impairs survival and behaviour at real-world exposure levels.